15.1k views
5 votes
What are the missing pieces to the steps? –27 = 4x2 – 24x –27 = 4(x2 – 6x) –27 + = 4(x2 – 6x + 9) 9 = 4(x – 3)2 = (x – 3)2 ± = x – 3 = x

User Frantz
by
5.8k points

2 Answers

1 vote
i think the 4 wasn't distributed correctly. it should be one of the first steps.

User Hushme
by
6.7k points
2 votes

Answer:

We can find out the missing pieces by the below explanation,

Here, the given equation,


-27 = 4x^2 - 24x

Step 1 :


-27=4(x^2-6x)

Step 2 :


-27+36=4(x^2-6x+9)

Step 3 :


9=4(x-3)^2

Step 4 :


(9)/(4)=(x-3)^2

Step 5 :


\pm (3)/(2)=x-3

Step 6 :


x=3\pm (3)/(2)

User Shvalb
by
6.0k points